Slow integration and weak institutional response to democratic challenges in UNASUR - Quispe Ponce, María Candelaria (2018)
In this paper the author presents the challenges of subregional integration faced by some South American states. They must ponder two phenomena: the dictatorial events in the region are usually caused by military coups led by conservative or progressive forces and the concentration of power in the executive branch disturbing checks and balances. In order to achieve the objectives of regional integration, it is necessary to analyse UNASUR experiences and difficulties regarding democracy and human rights; both are the criteria to assess the international conduct of states in the Americas.